Model to Improve the Energy Distribution Network through a Generator Set and Support with Capacitors to Satisfy the Maximum Demand in a Mining Site - Alvarado Laveriano, Walter Ramon (2024)
This research work describes a project to improve the electrical installations of a mining site in Peru due to energy shortage problems. The mining site is vital for the national production of silver, lead and zinc, which boosts the economy and generates employment. The lack of electricity supply affects ventilation in underground workings and other operations. The capacity of the existing generator sets does not cover the demand, and energy is rationalized, generating outages in the camp and other operational areas, affecting the quality of life of the collaborator. The improvement proposal consists of centralizing two generating sets in the same place, a main GE and an auxiliary one, an installation design is proposed that covers the sizing of the generating set to the power distribution, and applying reactive power compensation through capacitors. A model 3508TA generator set with a power of 680 KW is selected. The implementation of a 2.3kV medium voltage network is also proposed. The implementation of the model will be carried out considering safety regulations to preserve the health of the collaborator, the development of the activities of the mining site initially is at 35.6% after the implementation of the improvement model is calculated at an average of 84.5%, that is, there was an improvement of 48.9%. The validation of the project will be carried out using simulation software and specialized tools. In summary, the project seeks to solve the electricity supply problems in the mining site, improve operational efficiency and guarantee sustainable development in the future.